Pengaruh Model Pembelajaran Master Berbantuan Mind Mapping terhadap Kemampuan Pemecahan Masalah Matematika Siswa SMA Negeri 1 Sugihwaras - Luluk Nurhudaeni (Jurnal Pendidikan Madrasah, 2022)
This study aims to determine the influence of the mind mapping-assisted MASTER learning model on mathematical problem-solving ability. This type of research is a pseudo-experiment with the research design of the Post Test Only Control Group. The population of this study is all students of class XI MIPA SMA Negeri 1 Sugihwaras Bojonegoro for the 2018/2019 school year. Determination of the subject using cluster random sampling technique. Data are collected with a mathematical problem-solving ability test given to students in the form of a description test and given at the end of the study. Data analysis uses a one-tailed t-test with a 5% siginifiancy level. The results showed that thitung = .3 606938 > ttabel = 1 998341 so that H0 was rejected. Students' mathematical problem-solving ability using the mind mapping-assisted MASTER learning model is better than the ability to solve students' mathematical problems taught with conventional learning models. Thus, it can be concluded that there is an influence of the mind mapping-assisted MASTER learning model on students' mathematical problem-solving abilities.